2003
DOI: 10.1046/j.1439-0450.2003.00657.x
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in the Cerebellum of Dogs with Distemper

Abstract: Canine distemper virus (CDV) may induce multifocal demyelination in the central nervous system of infected dogs. The pathogenesis of this process is not clear. The present work identifies the presence of apoptotic cells in white and grey matter of dogs'cerebellum, naturally infected with CDV. Fifteen dogs with clinical signs of canine distemper that tested positive for CDV nucleoprotein were used. Brain specimens were processed and embedded in paraffin. Sections 5 microm thick were stained with hematoxylin-eos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 27 publications
3
24
0
1
Order By: Relevance
“…CDV infection caused apoptosis of Vero cells (30) and activated peripheral blood mononuclear cells in vitro (45). In vivo apoptosis was seen in the cerebellum and retropharyngeal lymph nodes of both naturally and experimentally CDV infected dogs (28,29). In vitro CDVeGFP infection of the canine cell lines CLGL-90 and 17-71 led to substantial cell death via apoptosis, as evidenced by the typical ''DNA laddering'' of genomic DNA and the increased binding of Annexin V (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…CDV infection caused apoptosis of Vero cells (30) and activated peripheral blood mononuclear cells in vitro (45). In vivo apoptosis was seen in the cerebellum and retropharyngeal lymph nodes of both naturally and experimentally CDV infected dogs (28,29). In vitro CDVeGFP infection of the canine cell lines CLGL-90 and 17-71 led to substantial cell death via apoptosis, as evidenced by the typical ''DNA laddering'' of genomic DNA and the increased binding of Annexin V (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Moro et al (2003b) and Kumagai et al (2004) observed that CD causes apoptosis in the lymph nodes. Moro et al (2003a) also observed apoptosis in the cerebellum, and Schobesberger et al (2005) observed that CDV infection induced apoptosis of lymphocytes and monocytes. Apoptosis can be triggered by various physiological and pathological stimuli, and it is prevalent in several immunosuppressive diseases of humans and animals (Ameisen and Capron, 1991;Lam and Vasconcelos, 1994).…”
Section: Introductionmentioning
confidence: 93%
“…In CDV-infected dogs apoptosis was reported to occur in vitro and in vivo (Guo and Lu, 2000;Moro et al, 2003a). Moro et al (2003b) and Kumagai et al (2004) observed that CD causes apoptosis in the lymph nodes.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that granular cells might enter apoptosis through direct lesion by CDV and secondary lesion as a result of previous glial cells impairment. Some searchers (13,14) reported apoptosis in astrocytic syncytia in vitro unlike these studies. Moro et all (14) reported TUNEL reaction in inclusion bodies, several gemistocytes, Gitter cells in white matter and the granular layer of grey matter.…”
Section: Discussionmentioning
confidence: 85%
“…In the case of CDV, cell death is observed during the infection (15). Some searchers reported that CD causes apoptosis in the brain and lymph nodes (7,12,13).…”
Section: Introductionmentioning
confidence: 99%